PRAGMATIC MEANINGS OF JAVANESE PHATIC MARKER ‘SAMPUN’: CULTURE-SPECIFIC PRAGMATIC PERSPECTIVE - R. Kunjana Rahardi (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The Javanese phatic marker ‘sampun’ draws several interpretations to researchers. The variety of interpretation poses communication problems in the daily communication, especially for people that do not fully understand the Javanese language and culture. The data consisted of excerpts of utterances transcribed from the recording tape of full conversations containing the phatic ‘sampun’ as discourse markers. The data gathering methods employed in this research were observation and speaking methods. Both types of data gathering methods employed the basic and advanced techniques in their elaboration. After being classified and typified properly, the data was analyzed using the distributional analysis method and pragmatic identity method commonly used in a linguistic research. The research showed the following results namely (1)the cultural context to emphasize intention, (2) the cultural context to emphasize the speaker’s hope and expectation, (3) the cultural context to emphasize the speaker’s intention to convince the hearer, (4) the cultural context to emphasize the speaker’s intention to question the hearer, (5) the cultural context to emphasize the speaker’s intention to agree, (6) the cultural context to convey disappointment, (7) the cultural context to emphasize the speaker’s inconvenience.